Measured maximal oxygen uptake in a multi-stage shuttle test and treadmill-run test in trained athletes - Aziz, A. R.; Chia, M. Y. H.; Teh, K. C. (The Journal of Sports Medicine and Physical Fitness, 2005)
Aim: The aims of the study were: i) to compare the measured maximal oxygen uptake (MV.O2max) during the 20 m multi-stage shuttle test (MST) with MV.O2max during an incremental treadmill-run test (TRT), and ii) to establish the reliability of MV.O2max during MST, in trained athletes. Methods: Experimental design: 8 well-trained endurance-athletes (END) and 8 athletes involved in team games (GAM) performed the MST twice (i.e. MST1 and MST2) and the TRT once, in 3 separate sessions. Measures: MV.O2max attained in the MST and TRT was measured using a portable respiratory analyser (model K4 RQ, Cosmed). Results: MV.O2max attained in the MST and TRT were significantly different for the END athletes (4.1±0.28 vs 4.45±0.31 L·min-1, P<0.05) but not for GAM athletes (4.01±0.51 vs 4.1±0.59 L·min-1, P>0.05). The 95% limits of agreement for MV.O2max in the MST in L·min-1 were -0.67 to 0.27. MV.O2max in MST1 and MST2 were not significantly different for END athletes (4.18±0.39 vs 4.1±0.28 L·min-1, P>0.05) and GAM athletes (4.01±0.55 vs 4.01±0.51 L·min-1, P>0.05). Reliability indicators for MV.O2max in L·min-1 for MST test-retest were: typical error (TE) = 0.14, coefficient of variation (CV) = 3.5 and intra-class correlation (ICC) = 0.90. Conclusion: MV.O2max in the MST was lower than that measured in the TRT for the END athletes but not for the GAM athletes. Sport-specificity was an important consideration, especially when testing END athletes for V.O2max. MV.O2max in the MST showed acceptable levels of reproducibility.